Public opinion of bureaucratic performance in Uttar Pradesh (India) and its impact on social change and modernization, 1966-1976 - Vajpeyi, Dhirenda K. (1978)
The hypothesis that greater citizen satisfaction tends to create greater support for governmental programs was tested in Uttar Pradesh, India over the past decade (1966-1976) using the panel study technique. In general,the attitudes and perceptions of the Indian citizens regarding the bureaucracy between 1966 and 1976 did not change considerably. They do not expect equal treatment and serious consideration of their opinions, feel that wealthy and influential persons stand better chances, and are quite critical of the bureaucracy. But despite this, citizens who reported associations with bureaucrats are generally supportive of the political system. An important finding of the study is the high discontent of the urban sample. The successful resolutions of this urban cynicism and other problems would direct and influence India's campaign for social change and modernization through democratic means.
Keywords: Public administration -- India; Public administration -- India -- Citizen participation; Public administration -- India -- Public opinion